Influence of thick lithomargic soil cover on Bouguer gravity low: Imprints from passive continental margin of southwestern India - P. Ajayakumar; N.F.K. Zeba (Geosystems and Geoenvironment, 2024)
The Periyar Plateau in central Kerala is characterized by a strong negative Bouguer gravity field around three major islands of a strongly negative field of the value of -150 mGal. Detailed gravity studies reveal that these islands of strong negative field are of a shallow nature and are not traceable in the 1/4° average gravity grids. Spectral analysis of Bouguer anomaly map and 2D gravity modelling of Periyar Plateau region reveal the average depth of the shallow source layer is as shallow as 700-1000 m, which is correlatable with the layer of lateritic/lithomargic soil cover and the underlying weathered country rock having a density of 2.2 g/cc. Such a strong influence on the regional gravity field is due to the wide contrast in the densities of the lateritic cover and the primary rocks of the basement. These results underline the need to recognize the strong influence of such alteration zones on the regional gravity fields, especially the tropics, a factor not always considered.